Feminisme dalam Kajian Ilmu Filsafat - Rahmadini, Miranda Ayu (Yayasan Sembilan Pemuda Indonesia, 2024)
This article explores the role of feminism in the study of philosophy with a focus on the development, contribution, and impact of the feminist movement on the discipline of philosophy. In this context, research discusses various feminist perspectives that influence the way of viewing key concepts in philosophy such as ethics, politics. The writing method is done by article review. Furthermore, it was found that the feminist movement aimed to change false beliefs about how women were looked down upon in various aspects of social life. Although it emerged as a result of the chaos and grievances of people in the West, it still spread throughout the world. This study also highlights the challenges, controversies, and contributions brought by feminist perspectives in enriching contemporary philosophical discourse. With this view in mind, this article offers a deep insight into the importance of feminism in expanding and enriching the realm of philosophy.